New soil test protocol for potentially available phosphorus in organic acidic soils - PATGIRI, PRITISHA; SWAMI, SANJAY; SINGH, SHUBHAM (Journal of Soil and Water Conservation, 2025)
A unique nutrient pool is evident in organic soils, unlike conventional soils. Lack of information of these pools results in imbalanced manuring schedule hindering successful production. The fraction of phosphorus (P) which is considered in soil testing under conventional system cannot justify the accurate degree of P in organic system. A distinct extractant that can extract the potentially available P in acidic organic system is needed. The current research aims to find out the best P extractant to extract the potentially available inorganic P pool. Five different sites (2 conventionally managed and 3 organically managed) were chosen. 5 organic acid extractants along with conventional Bray-1 (check) were employed. CRD was used for soil parameter analysis and Duncan’s Multiple Range Test (DMRT) was used for means comparison. Multiple linear regression was employed using SPSS and MS-excel for determining the best extractants. Among the 5 organic acid extractants, the contribution towards the P nutrition followed the order: 2, keto-glutaric acid > double lactate soluble P2O5 > citric acid soluble P2O5 > lactic acid soluble P2O5 > acetic acid soluble P2O5 (kg/ha). Regression analysis affirmed that 2% citric acid extractant and double lactate extractant were highly correlative to total P (R2=0.93). The combination of these two extractants can be claimed as the appropriate extractant to extract the potentially available inorganic P in organic farming system for P testing.